Butylphthalide Combined With Conventional Treatment Attenuates MMP-9 Levels and Increases VEGF Levels in Patients With Stroke: A Prospective Cohort Study - Xiong, Yingqiong; Liu, Juanjuan; Xu, Yang; Xie, Shu; Zhou, Xinhua; Cheng, Shaomin (Frontiers in Neurology, 2021)
Background and Purpose: Butylphtalide increases the vascular endothelial growth factor (VEGF) and decreases matrix metalloproteinase (MMP)-9 in animal models of stroke and might be of use in the management of stroke. To explore whether butylphthalide combined with conventional treatment can change the levels of MMP-9 and VEGF and the National Institutes of Health Stroke Scale (NIHSS) scores of patients with stroke. Methods: This was a prospective cohort study involving inpatients admitted to the Jiangxi Provincial People's Hospital (January–June 2019) due to acute cerebral infarction. The patients received conventional treatments with or without butylphthalide. The changes in the NIHSS scores were compared between groups. Plasma MMP-9 and VEGF were measured by enzyme-linked immunosorbent assay. Results: A total of 24 patients were included in the conventional treatment group and 46 in the butylphthalide group. The butylphthalide group showed lower MMP-9 (130 ± 59 vs. 188 ± 65, p = 0.001) and higher VEGF (441 ± 121 vs. 378 ± 70, p = 0.034) levels on day 6 compared with the conventional treatment group. The changes in MMP-9 and VEGF were significant, starting on day 3 in the butylphthalide group but on day 6 in the conventional treatment group. There were no differences between the two groups in the NIHSS scores at admission and at discharge (p > 0.05). The overall response rate was higher in the butylphthalide group compared with the conventional treatment group (63.0 vs. 37.5%, p = 0.042). Conclusion: Butylphthalide combined with conventional treatment can decrease MMP-9 levels and increase VEGF levels. The patients showed the reduced NIHSS scores, possibly suggesting some improvement in prognosis after stroke. Still, the conclusions need to be confirmed in a larger sample and in different etiological subtypes of stroke.